2000
DOI: 10.1002/1099-1611(200005/06)9:3<183::aid-pon446>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Body image dimensions and cancer: a heuristic cognitive behavioural model

Abstract: The term body image has been associated with a multitude of definitions within psychosocial oncology. It is well known that cancer and cancer treatments often have a negative impact on appearance‐related variables. A growing literature has emerged in recent years on the psychological aspects of changed appearance. This work has mainly addressed weight‐related appearance and the psychology of eating disorders. A number of themes have emerged from this work. These themes have been strongly influenced by a cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
135
0
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(152 citation statements)
references
References 35 publications
4
135
0
13
Order By: Relevance
“…Body image is defined as the mental picture of one's body, an attitude about the physical self, appearance, and state of health, wholeness, normal functioning, and sexuality. Body image is a component of a larger concept of self that for women includes feeling feminine and attractive (Mock, 1993;Carver et al, 1998;Hopwood, 1993;Cohen et al, 1998;White, 2000), enjoying one's body as a symbol of social expression, and as a way of being in the world (Cohen et al, 1998). The way in which one experiences her body is highly subjective, and is a product of her perceptions, thoughts, and feelings about body size, competence and function (Cohen et al, 1998;White, 2000).…”
Section: Body Image Sexuality and Sexual Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Body image is defined as the mental picture of one's body, an attitude about the physical self, appearance, and state of health, wholeness, normal functioning, and sexuality. Body image is a component of a larger concept of self that for women includes feeling feminine and attractive (Mock, 1993;Carver et al, 1998;Hopwood, 1993;Cohen et al, 1998;White, 2000), enjoying one's body as a symbol of social expression, and as a way of being in the world (Cohen et al, 1998). The way in which one experiences her body is highly subjective, and is a product of her perceptions, thoughts, and feelings about body size, competence and function (Cohen et al, 1998;White, 2000).…”
Section: Body Image Sexuality and Sexual Problemsmentioning
confidence: 99%
“…Body image is a component of a larger concept of self that for women includes feeling feminine and attractive (Mock, 1993;Carver et al, 1998;Hopwood, 1993;Cohen et al, 1998;White, 2000), enjoying one's body as a symbol of social expression, and as a way of being in the world (Cohen et al, 1998). The way in which one experiences her body is highly subjective, and is a product of her perceptions, thoughts, and feelings about body size, competence and function (Cohen et al, 1998;White, 2000). The significance of body image as a concept in the life of women was underscored in a study by Pikler and Winterowd (2003) who found that the better one's body image, the better women coped with cancer.…”
Section: Body Image Sexuality and Sexual Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is not yet a clear definition of body image in psycho-oncology (White, 2000), the most recent perspectives that have emerged in the mainstream body image literature consider this to be a multidimensional construct that encompasses cognitive, affective and behavioural components Pruzinsky, 1990, 2002;Jakatdar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…According to Demuth et al [12], a negative body image including distorted weight perception and body dissatisfaction was associated with psychosocial distress. Similarly, White [13] presented a model that suggests that perceived changes in appearance might lead to body image emotions such as depression. Additionally, distorted weight perception and body dissatisfaction were considered risk factors for depression during early adolescence [14].…”
Section: Introductionmentioning
confidence: 99%